2007
DOI: 10.1183/09031936.00060007
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of cystic fibrosis transmembrane conductance regulator in rat intrapulmonary arteries

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) gene encodes a cyclic adenosine monophosphate (cAMP)-dependent chloride channel located mainly at the apical membrane of epithelial cells. In myocytes of pulmonary arteries, numerous chloride channels have been identified and described, but not the CFTR. Thus the presence and function of the CFTR was investigated in rat intrapulmonary arteries.CFTR expression, localisation and function were analysed in cultured smooth muscle cells using Reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…Alternative hypothesis could be that genistein is a strong CFTR potentiator [36]. The latter has recently been demonstrated to be markedly involved in vasodilation [37][38][39]. In addition, genistein could act through its wide enhancing effects on the transcription of vasodilative proteins, some of them involving different tyrosine kinase activities.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative hypothesis could be that genistein is a strong CFTR potentiator [36]. The latter has recently been demonstrated to be markedly involved in vasodilation [37][38][39]. In addition, genistein could act through its wide enhancing effects on the transcription of vasodilative proteins, some of them involving different tyrosine kinase activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of CFTR in cells other than epithelium is now well documented (2,(26)(27)(28), its role in these cellular compartments, particularly in the endothelium, is not well known. Our work contributes to the understanding of the role of CFTR in lung endothelial cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Second, acute CFTR potentiation, in people with CF and the G551D-CFTR mutation, corrected smooth muscle abnormalities with improvements in airway distensibility and vascular tone (2). Finally, investigations by our group and others have shown that loss or inhibition of CFTR function in animal models can affect smooth muscle tone (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Collectively, these studies indicate that the asthma-like symptoms experienced by individuals with CF could be, in part, due to functional loss of CFTR.…”
Section: Introductionmentioning
confidence: 91%